1999
DOI: 10.1002/(sici)1098-0997(1999)7:5<227::aid-idog4>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative bacterial observations with group B streptococcal vulvovaginitis

Abstract: Objective: Group B streptococcal (GBS) vulvovaginitis is a poorly-delineated clinical entity. The purpose of this study is to report semiquantitative data from four cases of GBS vulvovaginitis and to comment on their significance in terms of the in vitro inhibitory capabilities of GBS.Methodology: Four patients whose clinical presentations were consistent with GBS vulvovaginitis, from whom GBS was isolated and for whom semi-quantitative as well as qualitative microbiologic data existed, were identified.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Multiple studies have found that S. agalactiae inhibits Lactobacillus spp. and G. vaginalis without inhibiting S. aureus (34)(35)(36) and that S. aureus colonization is significantly associated with colonization by S. agalactiae in a population of pregnant women (37). Our findings thus illustrate another way in which GBS could promote the virulence of S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that S. agalactiae inhibits Lactobacillus spp. and G. vaginalis without inhibiting S. aureus (34)(35)(36) and that S. aureus colonization is significantly associated with colonization by S. agalactiae in a population of pregnant women (37). Our findings thus illustrate another way in which GBS could promote the virulence of S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…The more severe the microscopic findings, the more likely these organisms will be cultured. Case studies have recently drawn attention to the possibility of vaginitis due to GBS [20], and Monif et al provide in vitro evidence that GBS inhibits growth of lactobacilli and G. vaginalis, but not S. aureus [21,22]. There is increasing evidence that some pregnant women develop mid-trimester chorioamnionitis caused by invasive GBS [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The more severe the microscopic findings, the more likely these organisms will be cultured. Case studies have recently drawn attention to the possibility of vaginitis due to group B streptococci 4 , and Monif et al provide in vitro evidence that group B streptococci inhibits growth of lactobacilli and G. vaginalis, but not S. aureus 22,23 . There is increasing evidence that some pregnant women develop mid-trimester chorioamnionitis caused by invasive group B streptococci 24,25 .…”
Section: Vaginal Fluid Constituents No Infection Candida Vaginitis Bamentioning
confidence: 99%